2009
DOI: 10.1158/0008-5472.can-08-4235
|View full text |Cite|
|
Sign up to set email alerts
|

Antitumor Activity of Gemcitabine and Oxaliplatin Is Augmented by Thymoquinone in Pancreatic Cancer

Abstract: Previous studies have shown biological activity of thymoquinone, an active compound extracted from Nigella sativa, in pancreatic cancer cells; however, preclinical animal studies are lacking. Here, we report, for the first time, the chemosensitizing effect of thymoquinone to conventional chemotherapeutic agents both in vitro and in vivo using an orthotopic model of pancreatic cancer. In vitro studies revealed that preexposure of cells with thymoquinone (25 Mmol/L) for 48 h followed by gemcitabine or oxaliplati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
173
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(182 citation statements)
references
References 37 publications
7
173
1
1
Order By: Relevance
“…Its utilization in combined therapies may be at lower dosage, reduce the dosage of the concomitant drug optimizing efficacy and toxicity and it might also overcome the drug resistance problem 30,31 . In previous studies, it has been reported that TQ led to a decrease in mean arterial blood pressure and heart rate in hypertensive rats in a dose dependent manner isoproterenol, cyclophosphamide and doxorubicin [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…Its utilization in combined therapies may be at lower dosage, reduce the dosage of the concomitant drug optimizing efficacy and toxicity and it might also overcome the drug resistance problem 30,31 . In previous studies, it has been reported that TQ led to a decrease in mean arterial blood pressure and heart rate in hypertensive rats in a dose dependent manner isoproterenol, cyclophosphamide and doxorubicin [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…The transcription nF-κB has been linked to cell proliferation, invasion, angiogenesis, metastasis and the suppression of apoptosis in pancreatic cancer (13)(14)(15)(16). Many conventional cancer chemotherapeutic agents, such as gemcitabine, vinblastine, vincristine, daunomycin, doxorubicin, campothecin, cisplatin and etoposide, have been shown to activate nF-κB (13,14,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…Many conventional cancer chemotherapeutic agents, such as gemcitabine, vinblastine, vincristine, daunomycin, doxorubicin, campothecin, cisplatin and etoposide, have been shown to activate nF-κB (13,14,16,17). There are numerous lines of evidence suggesting that nF-κB plays a major role in the growth and chemo -resistance of pancreatic cancer (12,18).…”
Section: Introductionmentioning
confidence: 99%
“…One of the good substitutions is the use of herbal medicine and one of the ancient herbs that was used medically for many diseases was black seed extract (23) . This herb has been used for many diseases since no signs of toxicity or serious side effects were known in antiquity (24) . The role of herbal medicine in allergic rhinitis as an effective therapy has not been studied extensively (15,16,17,25) and up to our knowledge, the use of topical N.S extract in treating A.R has not been studied yet.…”
Section: Discussionmentioning
confidence: 99%